Uwarunkowania wyników wyborów sejmowych w Polsce w 2005 r. = Conditioning of the results of the parliamentary elections in Poland in 2005 - Garbień, Anna; Krzeszowska, Katarzyna; Małkiewicz, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The run and results of the parliamentary elections in Poland which took place on 25th September 2005 are analyzed. The reasons behind the success of particular candidates and parties resulting from both actions taken in the past and from the tactic applied during the elections, especially professional marketing, are shown. It is pointed out that because of the low participation in the elections (40,57%) and great diffusion of votes, the real support given by the population as a whole to particular winning parties was very low: ?Prawo i Sprawiedliwość? - 10,54%, ?Platforma Obywatelska? - 9,42%, ?Samoobrona? - 4,46%, ?Sojusz Lewicy Demokratycznej? - 4,41%, ?Liga Polskich Rodzin? - 3,11%, ?Polskie Stronnictwo Ludowe? - 2,72%.
Keywords: Polska; wybory parlamentarne; historia; od 1989 r.